Pengelolaan Limbah Domestik di Dinas Lingkungan Hidup Kabupaten Lombok Timur - Jupri, Ahmad; Pratama, Hari Arya; Supardiono, Supardiono; Hidayati, Lilik; Fadli, Fadli; Husain, Pahmi (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
The problem of domestic waste in East Lombok Regency continues to increase along with population growth and community economic activities, so it requires an integrated and sustainable management system. This study aims to describe the domestic waste management system managed by the Environment and Forestry Service (DLHK) of East Lombok Regency and analyze the obstacles and development potential towards sustainable management. The research location consists of a domestic waste collection and sorting site, the Ijo Balit Final Processing Site (TPA), as well as the Integrated Waste Management Site (TPST) and TPS3R East Lombok. The research method uses a qualitative descriptive approach through participatory observation, in-depth interviews with DLH field officers and technical officials, as well as analysis of waste management regulations and technical guidelines. The results of the study show that the average daily waste generation reaches ±110 tons, with a composition of about 65% organic waste that has the potential to be processed into compost. Organic waste management is carried out at the Integrated Waste Management Site (TPST) or TPS3R through the stages of sorting, enumerating, aerobic composting, ripening, sieving, and packaging. The compost products produced are used for agricultural activities, reforestation, and productive plant cultivation. The controlled landfill system implemented at the Ijo Balit Landfill is in accordance with the principles of sustainable environmental management because it is equipped with leachate treatment facilities and methane gas capture channels. However, limited infrastructure, an uneven number of TPS3R, and low public awareness are still the main obstacles in effective waste management. This research emphasizes the need to increase infrastructure capacity, community education, and integration of local government and community programs as important strategies to realize effective and sustainable domestic waste management.